PENGGUNAAN MEDIA GAMBAR DALAM MENINGKATKAN PRESTASI BELAJAR MATEMATIKA MATERI PEMAHAMAN HUBUNGAN ANTAR SATUAN PANJANG - Utik Widarti Ningsih (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2017)
The study was aimed to describe the application of image media approaches to improve Mathematics learning achievement of Interpersonal Understanding long unit material at the third graders of the first state Elementary School Rejotengah, Deket - Lamongan in the academic year of 2010-2011 in the first semester. The study design was used in the form of action research within two cycles. Each cycle formed in spiral from one cycle to the next cycle. Each cycle included planning (plan), action (action), observation (observation), and reflection (reflection). The data collected by the test. From the results of the test in the form of a written test can be obtained significant results, i.e the value of the test results before action of 9 learners can be obtained sum value of 63 with an average of 7.0. After holding action, there was an increase amount of the value to 72 with an average of 8.0. Thus, the use of media images can improve matehmatics learning achievement Interpersonal Understanding long unit material.